Freedom from Fear - Reza Eslami; fatemeh Mortazavi fard (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2015)
This article first refers to the importance of the freedom from fear as a forgotten freedom, and analyzes the political fear and its negative impact on the citizens’ behavior in the society as well as the violation of human rights and freedoms. The article also provides the historical discourse on this freedom in renaissance era, and also reviews the elements required in achieving freedom from fear and its close relation to human security. The article then studies the threats to freedom of fear including classical threats such as arbitrary detention, torture, and forced disappearance as well as the new ones like terrorism, organized crimes, and domestic violence, and then examines the impact of these threats on freedom from fear. The article concludes that the basic human rights and fundamental freedoms cannot be achieved in any society without providing freedom from fear in its true sense and comprehensive meaning